Impact Of Early Mobilization On Postoprative Pain And Recovery: A Scoping Review - Wardani, Noor Ika; Ardiana, Anisah; Rondhianto, Rondhianto (Nursing Information Journal, 2025)
Early Postoperative pain remains a major clinical challenge that can delay recovery, increase healthcare costs, and diminish patients’ quality of life. Despite advancements in surgical techniques and analgesic protocols, many patients still experience moderate to severe pain in the immediate postoperative period. One key non-pharmacological intervention—early mobilization—has been shown to reduce pain intensity, enhance functional recovery, and minimize opioid use. However, the integration of early mobilization into routine postoperative care is frequently hindered by various systemic and patient-related barriers. These include anxiety about pain during movement, lack of staff training, and inconsistent implementation strategies across healthcare settings. As a result, the full benefits of early mobilization remain underutilized, particularly in vulnerable patient populations. This scoping review aimed to explore the clinical effectiveness, implementation challenges, and contextual factors affecting early mobilization in postoperative pain management. A systematic search of PubMed, Proquest, and ScienceDirect databases was conducted for peer-reviewed studies published between 2020 and 2025. Using the Joanna Briggs Institute (JBI) methodological framework, 35 studies out of 870 screened were included in the final analysis. The findings revealed that initiating mobilization within 48–72 hours after surgery significantly reduced pain and accelerated recovery, especially in orthopedic patients. However, patients undergoing abdominal or thoracic surgery experienced delayed mobilization due to incisional pain and mobility limitations. The review also identified key gaps in current research, particularly regarding the long-term effects of early mobilization on chronic pain, recovery sustainability, and its application in elderly or high-risk populations. Addressing these issues requires structured protocols, multidisciplinary involvement, and the adoption of digital health technologies to enhance implementation and accessibility.